LANGUAGE AND PERSUASION IN ATTIC ORATORY: IMPERATIVES AND QUESTIONS - Serafim, Andreas (AADEC - UNL, 2018)
This paper explores the persuasive potential of imperatives and questions in speeches of Aeschines and Demosthenes. Imperatives have a volitional-directive force in that they invite the audience to take action, either by blocking the speaker’s adversary from making a statement, or by voting against him (D. 19.75, 18.324; Aeschin. 3.156). The use of a high concentration of rhetorical questions at specific moments in speeches (Aeschin. 3.130-2; D. 19.250) becomes a powerful tool: both by articulating a relentless attack on the opponent, and by giving the audience no respite in which to consider flaws in the speaker’s position.